Utilising the Healy and Jenkin’s Research Teaching and Curriculum Design Nexus to transform undergraduate nursing research communities of practice - Naidoo, V.; Sibiya, M. N.; Padayachee, P. (South African Journal of Higher Education, 2023)
In science, research is known to be a diligent systematic inquiry into nature and society or both. It assists in validating and reﬁning existing knowledge and generating new knowledge. Lecturers and scholars have embraced the integration of evidence-based practice into the nursing education curriculum in numerous ways. Although the learning competencies necessary for research competencies amongst undergraduate nurses include an understanding of the basic concepts and processes of research methods, it does not adequately support student preparedness for the attainment of postgraduate research competencies. The design of this study adopted a qualitative, exploratory and descriptive course of enquiry that explored current pedagogical research practices amongst lecturers and supervisors. A case study approach utilising, specifically, a cross-case analysis helped provide a clear picture of institutional pedagogical practices related to the topic of inquiry and its implementation thereof. The cases from approved local, national and international higher education institutions formed the setting for the study. Lecturers facilitating and supervising undergraduate and postgraduate research studies comprised the target population of a purposive sampling selection. In this study, the authors utilised the Healey and Jenkins Teaching Nexus to show that the research engagement of students and nursing research communities of practice can be strengthened if embraced by sound pedagogical practices. The Nexus outlines four concepts that guide the pedagogical practice of the research module that promotes undergraduate students as researchers. The authors of this article concluded that it was necessary to engage students as producers and not merely as consumers of knowledge. In this study, the researchers also utilised the Nexus to show students’ engagement in fostering different teaching approaches to research knowledge acquisition.